EVALUATION OF TECHNOLOGICAL AND ECONOMIC EFFICIENCY OF THE INTRODUCTION OF A VARIABLE-FREQUENCY DRIVE AT THE CHAUN HEAT AND ELECTRICITY DISTRIBUTION ENTERPRISE - A.K. Reshelyan (Zenodo, 2023)
This article presents the results of the analysis of the operation of the network pumping unit of the Chaun enterprise for the distribution of heat and electricity, taking into account the prospects for the development of the city of Pevek of the Chukotka Autonomous District, the need to replace pumping equipment is substantiated, the performance of pumping units that meet the requirements of operation in the technological minimum mode is determined. The calculation of economic efficiency from the introduction of adjustable electric drives at the pumping unit of the Chaun enterprise for the distribution of heat and electricity is made, the necessary measures for labor protection during the installation and operation of these electric drives are described.